2008
DOI: 10.1897/07-523.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of perfluorooctane sulfonic acid and perfluorooctanoic acid on freshwater macroinvertebrates (Daphnia magna and Moina macrocopa) and fish (Oryzias latipes)

Abstract: Because of their global distribution, persistence, and tendency to bioaccumulate, concerns about perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) are growing. We determined the toxicity of PFOS and PFOA in several freshwater organisms, including two cladocerans, Daphnia magna and Moina macrocopa, and the teleost Oryzias latipes. In general, PFOS is approximately 10 times more toxic than PFOA in these organisms. In M. macrocopa, the median lethal concentration (LC50) was 17.95 mg/L for PFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
71
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 31 publications
9
71
2
Order By: Relevance
“…Higher concentrations of PFOS delayed time of first litter. This tendency was consistent with earlier observations, in which toxicity usually prolonged the time of flea reproduction (Ji et al, 2008). The quantity of first brood decreased initially and then rose and fell as the concentration increased.…”
supporting
confidence: 93%
“…Higher concentrations of PFOS delayed time of first litter. This tendency was consistent with earlier observations, in which toxicity usually prolonged the time of flea reproduction (Ji et al, 2008). The quantity of first brood decreased initially and then rose and fell as the concentration increased.…”
supporting
confidence: 93%
“…Based on the results of this study, PFOA is less toxic than PFOS to aquatic invertebrates, and this finding is in a good agreement with previous studies. 19,30) The 21-d LC 50 and survival NOEC values of Daphnia magna exposed to PFOA in this study are greater than 100 mg/l and are similar to those reported by Colombo et al 11) In their recently published study, the EC 50 and survival NOEC of Daphnia magna were reported to be greater than 88.6 mg/l after 21 days exposure. Compared with published data on the chronic toxicity of PFOS, the 21-d survival NOEC of 5 mg/l found for Daphnia magna in this study is similar to the value of 5.3 mg/l for Daphnia magna in the study of Boudreau et al, 16) but the 21-d LC 50 of 9.1 mg/l found for Daphnia magna in this study is lower than the 21-d LC 50 of 42.9 mg/l for Daphnia magna reported in the same study.…”
Section: Discussionsupporting
confidence: 90%
“…After 21 days of PFOA exposure, the survival NOEC was greater than 100 mg/l, while the reproduction NOEC was 10 mg/l in Daphnia magna. Compared to recently published studies, the reproduction NOEC value of PFOA found for Daphnia magna in this study was similar to the reproduction NOEC value of 20 mg/l reported by Colombo et al 11) and 12.5 mg/l by Ji et al 30) After 21 days of PFOS exposure, the survival NOEC was 5 mg/l, while the reproduction NOEC was 1 mg/l in Daphnia magna. The NOEC value of PFOS in this result is also similar to the value of 1.25 mg/l reported by Ji et al for Daphnia magna.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Perfluorooctane sulfonic acid is reported to cause reproduction-related effects in Japanese medaka (Oryzias latipes); the parental exposure to PFOS affected the performance of offspring, such as hatchability, swim-up success, and survival. The continuous exposure from parent to progeny generation increased the extent of such adverse effects [8]. Reports say that PFOS can induce hepatotoxicity, resulting in histopathological changes in the zebrafish liver [9].…”
Section: Introductionmentioning
confidence: 99%